Striking a balance between innovation and standards: A study of teachers implementing project-based approaches to teaching science - Toolin, Regina E. (Journal of Science Education and Technology, 2004)
This research reports on the efforts of six middle school and high school science teachers in a public school district in New York City to balance innovative teaching methods and strategies with the New York State Learning Standards and Regents requirements. More specifically, this research examines the factors that influenced the implementation of project-based approaches to teaching and learning science. Observations of meetings and classrooms, and collection of artifacts such as curricula, project planners, demographic profiles, student work, and test results served as the primary data sources that were triangulated and related to current theory on project-based learning in science. Four teachers embraced aspects of project-based learning in science and two rejected most aspects of teaching project-based learning in science. Implications for science professional development are discussed.
Keywords: apprentissage par projet; enseignement secondaire; innovation pédagogique; sciences